PENGARUH PENGGUNAAN APLIKASI SISTEM INFORMASI ABSENSI ONLINE TERHADAP KINERJA PEGAWAI DINAS SOSIAL KABUPATEN SUMBAWA BARAT - SYUKRIYATI, HARNIDA NURUS; ZAINUDDIN, ZAINUDDIN; APRIANSYAH, ALDI (GANEC SWARA, 2023)
Improving employee discipline and service quality in the public sector, especially in the West Sumbawa Regency Social Service, is a crucial aspect in meeting community needs. The main factor found to influence service quality is the level of employee discipline. This research aims to analyze the effect of using the Online Attendance Information System application on the discipline of West Sumbawa Regency Social Service employees. Quantitative methods are used by applying statistical analysis, including Pearson correlation and simple linear regression. The research sample involved 48 respondents from the West Sumbawa Regency Social Service, and data was collected through a questionnaire designed to evaluate employee discipline, use of SIAO, and service quality. The results of the analysis show a significant relationship between employee discipline and service quality, with the Online Attendance application having a positive impact. The implementation of SIAO in the West Sumbawa Regency Social Service has proven effective in improving employee discipline, which makes a positive contribution to improving service quality. These results strengthen the validity and reliability of SIAO as a consistent and valid measuring tool to support improvements in employee discipline and service quality. The online attendance information system (SIAO) has had a positive impact in improving employee discipline and directly improving the quality of services at the West Sumbawa Regency Social Service